2017
DOI: 10.1112/plms.12086
|View full text |Cite
|
Sign up to set email alerts
|

Drinfeld double of GLn and generalized cluster structures

Abstract: We construct a generalized cluster structure compatible with the Poisson bracket on the Drinfeld double of the standard Poisson–Lie group GLn and derive from it a generalized cluster structure on GLn compatible with the push‐forward of the Poisson bracket on the dual Poisson–Lie group.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
130
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(134 citation statements)
references
References 19 publications
4
130
0
Order By: Relevance
“…First, let us recall the definition of the generalized cluster algebras of geometric type (see [4,7]).…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…First, let us recall the definition of the generalized cluster algebras of geometric type (see [4,7]).…”
Section: Preliminariesmentioning
confidence: 99%
“…Gekhtman, Shapiro and Vainshtein [7] proved that generalized upper cluster algebras over certain rings retain all properties of ordinary upper cluster algebras, and under certain coprimality conditions coincide with the intersection of rings of Laurent polynomials in a finite collection of clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Muller showed that locally acyclic cluster algebras coincide with their upper cluster algebras in [11]. Gekhtman, Shapiro and Vainshte in [8] proved (a) for generalized cluster algebras, then Bai, Chen, Ding and Xu demonstrated (c) and the sufficiency of (b) in [1]. Besides, Bai discovered that acyclic generalized cluster algebras coincide with their generalized upper cluster algebras.…”
Section: Introductionmentioning
confidence: 96%
“…In the theory of cluster algebras, the following are interesting conjectures on seeds of cluster algebras: in a cluster algebra of rank n, (1) each seed is uniquely defined by its cluster; (2) any two seeds with n − 1 common cluster variables are connected with each other by one step of mutation. One can refer [3,8] for detailed proof.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation